Pembentukan Karakter Anak Usia Dini Melalui Perkembangan Sosial Emosional di TK Dahlia Kecamatan Telaga - Salsabila R Solang; Nayla Faradilla; Haryanti Huna; Sri Aginda Nambo (Prodi Sastra Jepang Universitas Ngudi Waluyo, 2025)
Early childhood social-emotional development is an important foundation in shaping children's readiness to face the world of education and social life. This study aims to describe the social-emotional development of children in Dahlia Kindergarten, Telaga District, which includes aspects of self-awareness, emotion management, pride, shame and guilt, empathy, sharing, cooperation, respect for others, independence, and discipline. The methods used in this study were observation, interviews, and child development checks. The study subjects amounted to 36 children consisting of 16 children of group A and 20 children of group B. The results showed that most of the children showed good social-emotional development, although there were 6 children who still had difficulties in managing emotions. The learning environment at Dahlia Kindergarten is considered quite supportive, with teachers and principals playing an active role in instilling social values through various fun and interactive learning activities. In addition, parental involvement through regular communication with the school also contributes to the consistency of the formation of children's social behavior at home. Overall, these results show that with proper stimulation and conducive environmental support, the child's social-emotional development can be optimally enhanced.